1985
DOI: 10.1111/j.1365-2621.1985.tb01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential value of the Limulus lysate assay for the measurement of meat spoilage

Abstract: Using a microtitre plate method the Limulus lysate endotoxin assay was shown to be capable of detecting Pseudomonas spp. at viable cell concentrations of 102-l@1/ml. The changes in endotoxin concentration, microbial flora, pH and ERV of laboratoryproduced minced beef and minced pork stored at 4°C were monitored. The endotoxin concentration was shown to increase with the onset of spoilage. Factors were derived enabling an estimate of AMC to be made from the endotoxin concentration determined by the Limulus lysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…The accumulation of TLR2‐ and TLR4‐stimulants was minimized by storing meats in the intact, rather than in the minced form, and by storage under a modified atmosphere, rather than exposed to air. Stimulants of both TLRs correlated well with bacterial counts, which were very similar to those reported in previous studies of microbial growth in minced meat products stored in air or under a modified atmosphere (Fallowfield and Patterson 1985; Lambropoulou and others 1996; Jay and others 2003). This information, taken together with the results from our previous studies that showed that meat‐derived TLR‐stimulants are not likely to be SFAs (Erridge and Samani 2009) and are inhibited by both polymyxin‐B and oxidized palmitoyl‐arachidonyl‐phosphatidyl choline (Erridge 2010), strongly suggest that the TLR2‐ and TLR4‐stimulants identified in meats are of bacterial origin, being presumably BLPs and LPS, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The accumulation of TLR2‐ and TLR4‐stimulants was minimized by storing meats in the intact, rather than in the minced form, and by storage under a modified atmosphere, rather than exposed to air. Stimulants of both TLRs correlated well with bacterial counts, which were very similar to those reported in previous studies of microbial growth in minced meat products stored in air or under a modified atmosphere (Fallowfield and Patterson 1985; Lambropoulou and others 1996; Jay and others 2003). This information, taken together with the results from our previous studies that showed that meat‐derived TLR‐stimulants are not likely to be SFAs (Erridge and Samani 2009) and are inhibited by both polymyxin‐B and oxidized palmitoyl‐arachidonyl‐phosphatidyl choline (Erridge 2010), strongly suggest that the TLR2‐ and TLR4‐stimulants identified in meats are of bacterial origin, being presumably BLPs and LPS, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the limulus system is insensitive to BLPs, and so cannot be used for their quantification (Erridge and Samani 2009). Despite these limitations, however, the LAL assay has been used previously to demonstrate that the endotoxin content of spoiling meat correlates well with microbial load, a finding supported by the present study (Fallowfield and Patterson 1985; Jay and others 1979). The LAL assay has also been used to estimate the amount of endotoxin present in minced beef stored at refrigeration temperature for 6 d to range from approximately 32 μg/g to approximately 2.5 mg/g (Jay and others 1979; Fallowfield and Patterson 1985).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations